STUDI MAKNA LOGO INDONESIA HALAL INDUSTRY AWARDS (IHYA) TERHADAP PERSEPSI PELAKU INDUSTRI KOTA PADANG PANJANG - Inayah, Alifia Rifki; Ditto, Anin; Yanti, Eva (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2023)
Reasearch for analyze meaning of Indonesia Halal Industry Awards (IHYA) logo using the semiotic theory of Charles Sanders Peirce and Roland Barthes, to see how the semiotic elements in the logo represent halal industry, on the views of halal industry players in Padang Panjang city. IHYA logo carries halal value by redefining the meaning. This study uses descriptive qualitative methods, using visual perception theory, Peirce's and Barthes’ semiotics. With visuals that redefine the meaning of halal, it produces the perception of halal industry players in the city of Padang Panjang which causes prejudice against the IHYA logo, because of the lingering old ethics about the iconic halal identity. So the analytical approach of Peirce's semiotic theory that reveals signs, objects, interpretants with further meanings of Barthes' semiotic theory in the meaning of the level as an effort to clarify the true meaning of the IHYA logo.